(untitled) (Studia Prawnicze / The Legal Studies, 1984)
The work is a monograph on groundless enrichment in Roumania. The author discusses: specific situation in the field of sources’ of groundless enrichment (civil code of 1964 modelled after the Napoleon code only partially regulates the problem); strictly subsidiary character of groundless enrichment ascribed to this institution by the doctrine and judicial decision; premises of claim to return (enrichment, impoverishment ,relation between them at present described as rather genetic than causative link); principles of return of enrichment (object and scope similar to Roman one). It should be stressed that the return; ad the enrichment embraces only an obligation to return actually existing enrichment. A characteristic feature of Roumania is that the institution of groundless enrichment is a constructure of judicial decisions and the doctrine which made use of weak normative grounds regulating some kinds of condictions. Therefore the author stresses particular problems against the background of judicial decisions. A very rigorous attitude towards the problem of auxiliarity of groundless enrichment should be stressed, which sometimes artificially constructs a contract where its existence is doubtful in order to avoid the reference to the provisions on groundless enrichment. According to Romanistic tradition, groundles enrichment should be considered a quasi-contract; at present such filiation has been questioned and groundless enrichment is considered independent source of obligation. A characteristic feature is that in Roumania issues connected with foul prestation have not been separately regulated. This results in many difficulties connected with imperfection of solutions which either provide for giving the enrichment to the solven’s or leaving it with the accipients. The work gives some information de lege ferenda.